The Nazi officer's wife how one Jewish woman survived the Holocaust - Beer, Edith Hahn (Perennial, 2000)
Edith Hahn tells how she survived the Holocaust, first by going underground, using a Christian friend's identity papers, and eventually marrying Werner Vetter, a Nazi Party member who knew she was Jewish.